Spinal cannabinoid receptor 2 activation reduces hypersensitivity associated with bone cancer pain and improves the integrity of the blood–spinal cord barrier. Issue 10 (12th October 2020) - Wang, Chenchen; Xu, Ke; Wang, Yu; Mao, Yanting; Huang, Yulin; Liang, Ying; Liu, Yue; Hao, Jing; Gu, Xiaoping; Ma, Zhengliang; Sun, Yu'e
Abstract : Background: Disruption of the blood–spinal cord barrier (BSCB) can facilitate inflammation that results in pain hypersensitivity. Proinflammatory cytokines produced by activated microglia and astrocytes damage the BSCB. This study aims to explore whether the BSCB is damaged in the bone cancer pain (BCP) model and to investigate a potential role and mechanism of JWH015 ((2-methyl-1-propyl-1H-indol-3-yl)−1-naphthalenylmethanone), a selective cannabinoid receptor 2 (CB2R) agonist, in preserving the BSCB integrity in the BCP model. Methods: We used a male mouse model of BCP. Pain hypersensitivity was measured over time. Evans blue dye extravasation, transmission electron microscopy and Western blotting were performed to investigate the permeability and structural integrity of the BSCB. Immunofluorescence staining and western blotting were used to investigate the effect of JWH015 on the activation of glial cells and the levels of proinflammatory cytokines. Results: A single intrathecal injection of JWH015 ameliorated pain hypersensitivity, the BSCB disruption and microglia and astrocyte activation. Decreases in the expression of ZO-1 and claudin-5 were partially restored by JWH015. The levels of the proinflammatory cytokines interleukin-1β and tumor necrosis factor-α and the enzyme MMP9 were reduced by JWH015. However, all effects were prevented by pretreatment with a CB2R-selective antagonist, AM630 ((6-iodo-2-methyl-1-(2-morpholinoethyl)−1H-indol-3-yl)(4-methoxyphenyl)methanone). Conclusions: JWH015 alleviates neuroinflammation and maintains the BSCB integrity and permeability in a mouse model of BCP, which is probably mediated by inhibiting glial cells activation. This study reveals the new analgesic mechanism of JWH015 on BCP and provides a perspective to explore novel drugs that target the BSCB to control BCP.